Pengetahuan Masyarakat Lokal Terkait Keberadaan Kepiting Tapal Kuda dan Distribusinya di Sepanjang Pesisir Pulau Bintan - Rika Anggraini; Ita Karlina (Universitas Diponegoro, 2023)
There are many reports of a decline in the population of horseshoe crabs in Asia, but knowledge about the distribution of horseshoe crabs on the coast of Bintan Island is still limited. We conducted interviews in 15 locations on the coast of Bintan Island. The information we collect is about the distribution of potential spawning areas and the utilization of horseshoe crabs in each area. Respondents were randomly selected as the surveyor walked through each study site. Verification of the distribution and breeding grounds of horseshoe crabs by respondents was done by asking respondents to indicate the location where they had seen pairs of horseshoe crabs mating, juveniles, and horseshoe crab eggs met; we also validated with direct observations made in the field. Respondents reported that in 15 locations, they had seen juveniles and horseshoe crabs in pairs. One respondent directly observed horseshoe crab eggs on the beach, and only a few found horseshoe crabs laying eggs. Respondents who saw paired horseshoe crabs generally worked as fishermen. We found three juvenile locations for horseshoe crabs, namely at Tembeling, Pengujan and Pengudang locations. At three locations Tachypleus gigas and Carcinoscorpius rotundicauda were found. Horseshoe crabs on Bintan Island are used as fertilizer, medicine and wall decoration. In this study, local wisdom provides essential information regarding the potential distribution of spawning grounds and the utilization of horseshoe crabs on the coast of Bintan Island Banyaknya laporan mengenai penurunan populasi kepiting tapal kuda di Asia, tetapi pengetahuan tentang distribusi kepiting tapal kuda di Pesisir Pulau Bintan terbatas. kami melakukan wawancara di 15 lokasi di pesisir Pulau Bintan. Informasi yang kami kumpulkan tentang distribusi potensi daerah pemijahan, dan pemanfaatan kepiting tapal kuda pada masing-masing daerah. Responden dipilih secara acak pada saat pihak survei berjalan menyelusuri setiap lokasi penelitian. Verifikaksi distribusi dan tempat pembibitan kepiting tapal kuda oleh responden dilakukan dengan meminta responden untuk menunjukkan lokasi yang pernah melihat sepasang kepiting tapal kuda kawin, juvenil, serta telur kepiting tapal kuda di temui, kami juga melakukan validasi dengan pengamatan langsung yang di lakukan di lapangan. Responden telah melaporkan bahwa pada 15 lokasi pernah melihat juvenil dan kepiting tapal kuda berpasangan. Ada satu responden yang secara langsung mengamati telur kepiting tapal kuda di pantai dan hanya sebagian yang menemukan kepiting tapal kuda bertelur. Responden yang melihat kepiting tapal kuda berpasangan pada umumnya yang berkerja sebagai nelayan. Kami menemukan 3 lokasi juvenil kepiting tapal kuda yaitu pada lokasi Tembeling, Pengujan dan Pengudang. Pada ketiga lokas tersebut ditemukan jenis Tachypleus gigas dan Carcinoscorpius rotundicauda. Kepiting tapal kuda di Pulau Bintan di manfaatkan sebagai pupuk, obat dan hiasan dinding. Dalam penelitian ini pengetahuan lokal memberikan infromasi penting mengenai distribusi potensi lokasi pemijahan dan pemanfaatan kepiting tapal kuda di pesisir Pulau Bintan.